Cognitive functioning and work-related outcomes of non-central nervous system cancer survivors: protocol for a systematic review with meta-analysis. Issue 7 (12th July 2022) - Oliveira, Ana F; Fernandes, Sofia; Reis, Juliana D; Torres, Ana; Santos, Isabel M; Von Ah, Diane
Abstract : Introduction: In recent years, growing attention has been given to the study of the impact of cancer-related cognitive impairment (CRCI) in working non-central nervous system (CNS) cancer survivors. Available literature has shown that working cancer survivors identify cognitive problems at work as very problematic and worrisome. Some reviews have discussed the association between CRCI and work-related outcomes; however, none to date have investigated this association through comprehensive systematic review with meta-analysis. Hence, this work will comprehensively summarise existing evidence from quantitative studies assessing the relationship between CRCI and work-related outcomes of adult non-CNS cancer survivors at working age. Methods and analysis: The systematic review procedures and its report will follow the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement. Electronic searches in the databases Web of Science, Scopus, PubMed, ProQuest, PsycINFO and CINAHL, complemented by a manual search of other relevant articles, will be performed from 2000 onwards to identify relevant publications. Two independent reviewers will assess studies for inclusion and extract data from each article using a standardised form. Studies eligible for inclusion must be quantitative, contain adult non-CNS cancer survivors with CRCI, and a measure of cognitive functioning and work-related outcomes. To assess risk of bias, the Joanna Briggs Institute Critical Appraisal Tool Studies checklists will be independently used by the two researchers. Synthesis of the included articles will be conducted using a narrative method and through meta-analysis. Meta-analysis will be reported via correlation for the association between CRCI and work-related outcomes. The cumulative evidence will be assessed using the Grading of Recommendations Assessment, Development and Evaluation system. Ethics and dissemination: Ethics approval is not required since individual patient data will not be collected. The findings will be published in a peer-review indexed journal, presented at scientific meetings and included in a chapter of a Doctoral thesis. PROSPERO registration number: CRD42020165458.